Central bank transparency and financial market expectations: The case of emerging markets - Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
In this paper, we study the influence of central bank transparency on the formation of money market expectations in emerging markets. The sample covers 25 countries for the period from January 1998 to December 2009. We find, first, that transparency reduces the bias (the difference between the money market rate and the weighted expected target rate over the contract period) in money market expectations. The effect is larger for non-inflation targeters, countries with low income, and countries with low financial depth. However, the biasreducing effect of transparency prevails only if inflation is relatively low. Second, three subcategories of the Eijffinger and Geraats (2006) lead to a smaller bias in expectations: operational, political, and economic transparency, with the effect being the largest for operational transparency. Finally, an intermediate level of transparency is found to have the most favourable influence on money market expectations. Neither complete secrecy nor complete transparency is optimal.
Keywords: E52; E58; 330; central bank transparency; emerging markets; financial market expectations; interest rates; monetary policy; money market; Geldpolitik; Informationsverhalten; Staatliche Information; Wirkungsanalyse; Geldmarkt; Zins; Erwartungstheorie; Zins; Geldpolitik; Aufstrebende Märkte; Schwellenländer